Time‐dependent relative potency factors for polycyclic aromatic hydrocarbons and their derivatives in the H4IIE‐luc bioassay. (26th February 2014) - Larsson, Maria; Hagberg, Jessika; Giesy, John P.; Engwall, Magnus
Abstract The H4IIE‐luc transactivation bioassay for aryl hydrocarbon receptor (AhR) agonists was used to investigate the relative potency factors (REPs) of 22 individual polycyclic aromatic hydrocarbons (PAHs) and their oxygenated‐, methylated‐, and N‐containing derivatives (azaarenes), which are often present in PAH‐contaminated soils. Naphthacene and dibenz[ah]acridine exhibited greater AhR‐mediated potency, whereas lesser molecular–weight azaarenes were less potent AhR agonists. Six oxygenated PAHs had calculable REPs, but their potencies were less than their parent PAHs. Unlike the parent, unsubstituted PAHs, oxidation of methylated PAHs seemed to increase the AhR‐mediated potency of the compounds, with 2‐methylanthracene‐9, 10‐dione being almost 2 times more potent than 2‐methylanthracene. Both bioassay and gas chromatography–mass spectrometry analysis were used to examine the exposure time–dependent effects on the REPs at 24 h, 48 h, and 72 h of exposure in the H4IIE‐luc transactivation bioassay. Changes in concentrations of 5 compounds including the model reference 2, 3, 7, 8‐tetrachlorodibenzo‐p‐dioxin in the cell culture wells were measured, and the amounts in the cell medium, in the cells, and adsorbed to the wells was determined and the influence on the REPs was studied. Declining REP values with increased duration of exposure were shown for all compounds, which we concluded were a consequence of the metabolism of PAHs and PAH derivatives in H4IIe‐luc cells. The present study provides new knowledge regarding the degradation and distribution of compounds in the wells during exposure. Environ Toxicol Chem 2014;33:943–953. © 2014 SETAC